2022
DOI: 10.1002/jeq2.20366
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of nitrogen fertilizer timing on nitrate loss and crop production in northwest Iowa

Abstract: In the U.S. Midwest, nitrate in subsurface tile drainage from corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] systems is detrimental to water quality at local and national scales. The objective of this replicated plot study in northwest Iowa, performed in 2015–2020, was to investigate the influence of nitrogen (N) fertilizer timing on crop production and NO3 load in subsurface (tile) drainage discharge. Four treatments applied to corn included fall anhydrous ammonia with a nitrification inhibitor (F), spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The SPARROW modeling results in Table 1 suggest that neither the 59% nor the 45% nitrogen loading reduction targets can be achieved by better management of fertilizer alone. This is confirmed by in‐field experiments such as those in Iowa (Waring et al., 2022), which evaluated fertilizer application timing and concluded that while split application produced modest reductions in nitrate concentration in subsurface drainage discharge, fertilizer nitrogen management alone could not be enough to reduce nitrate load to surface water systems. Continued efforts to improve nitrogen use efficiency can nevertheless make further contributions to controlling the size of the hypoxic zone in the Gulf of Mexico.…”
Section: What Management Practices Can Contribute To Mitigation?mentioning
confidence: 82%
“…The SPARROW modeling results in Table 1 suggest that neither the 59% nor the 45% nitrogen loading reduction targets can be achieved by better management of fertilizer alone. This is confirmed by in‐field experiments such as those in Iowa (Waring et al., 2022), which evaluated fertilizer application timing and concluded that while split application produced modest reductions in nitrate concentration in subsurface drainage discharge, fertilizer nitrogen management alone could not be enough to reduce nitrate load to surface water systems. Continued efforts to improve nitrogen use efficiency can nevertheless make further contributions to controlling the size of the hypoxic zone in the Gulf of Mexico.…”
Section: What Management Practices Can Contribute To Mitigation?mentioning
confidence: 82%
“…Both the river pollution index (RPI) and the water quality index use the concentrations of NH 3 -N and DO as the primary indicators of river water quality (Fortuna et al, 2023;Tsai et al, 2021). NH 3 -N pollution mainly comes from anthropogenic sources such as the use of agricultural fertilizers on land (Dutra et al, 2016;Waring et al, 2022). WT significantly affects the inactivation/degradation of the physical, chemical, and biological processes within aquatic systems (Schijven et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, measurements from tile lines that drain individual field research plots have long been utilized to study nutrient leaching (Baker et al., 1975). Although tile drainage studies have been crucial in helping to establish relationships between management practices and nutrient losses (Lawlor et al., 2008; Waring et al., 2022), there are several potential limitations.…”
Section: Introductionmentioning
confidence: 99%